Sappho-Nieuws. (Gent : Sappho, 1975)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijksRedactie : Hertstraat 1A, 9000 Gent ; vanaf (1978) jun : Ottogracht 33-37, 9000 Gent ; vanaf (1979) mei : Gebr. Van Eyckstraat 7, 9000 Gent
Nederlands
Periodiek